EVALUATING OCCUPATIONAL TRAINING IN NINEVEH CENTER FOR AGRICULTURAL EXTENSION AND TRAINING FROM THE TRAINEES POINT OF VIEW - Aamel Fadhel Khalil Al-Abbassi (Mesopotamia Journal of Agriculture)
The main objectives of the present research are to evaluate occupational training in Nineveh center for agricultural extension and training from the trainees point of view in the following aspects: objectives of training course, selecting the trainees, training content, methods and training aids, requirements of implementation and training environment, trainers efficiency and training results, to identify differences in training results according to some personal and vocational characteristics of the trainees. The number of trainees were 89. which participated in nine occupational training courses held on Nineveh center for agricultural extension and training during1/march/2007upto 30/june/2008. The data were collected through questionnaire, included personal and vocational characteristics of trainees and 7 aspects for training evaluation. After collecting the data following statistical methods were used (means and percentage weight, Mann-Whittney test and Kurskal-Wallis test). The results showed that more than 80% of the trainees evaluation of occupational training in Nineveh center for agricultural extension and training was medium to high, and the aspect of trainers efficiency came in the first rank when arranged by the trainees with percentage weight 82.233%, while the aspect of methods and training aids came at last 72.066%. The results also showed no significant differences in training results according to: academic qualification, years of employment, pre-training in course subject, occupation ambition and desire to innovativeness, while difference was found in trainees specilization in training course subject.